Major process equipment maintenance and repair - Bloch, Heinz P., 1933-; Geitner, Fred K. (Houston, Tex. : Gulf Pub. Co., 1997)
This updated edition is an invaluable source of practical cost-effective maintenance, repair, installation, and field verification procedures for machinery engineers. It is filled with step-by-step instructions and quick-reference checklists that describe preventive and predictive maintenance for major process units such as vertical, horizontal, reciprocating, and liquid ring vacuum pumps, fans and blowers, compressors, turboexpanders, turbines, and more. Also included are sections on machinery protection, storage, lubrication, and periodic monitoring. A new section examines centrifugal pumps and explains how and why they continue to fail. More new information focuses on maintenance for aircraft derivative gas turbines. This revised edition gives special attention throughout to maintenance and repair procedures needed to ensure efficiency, performance, and long life.
Part I: Installation and Repair of Major Process Equipment. Installation, maintenance, and repair of horizontal pumps. Installation, maintenance, and repair of vertical pumps. Reciprocating and liquid ring vacuum pumps. Positive displacement and dynamic blowers. Reciprocating gas engines and compressors. Part II: Maintenance for Power Generation and Transmission. Power transmission gears. Installation and maintenance of V-belt drives. Steam turbines and turboexpanders. Gas turbines. Maintenance of hydraulic governors disassembly. Maintenance of electric motors and associated apparatus. Part III: General Preventive and Predictive Maintenance. Storage protection and lubrication management. Vibration and condition monitoring. Maintainability considerations. Index.
"Pumps, fans and blowers, mixers, compressors, turboexpanders, motors, turbines."
Includes bibliographical references and index.
Keywords: Chemical plants -- Equipment and supplies -- Maintenance and repair; Machines; Onderhoud; Electronic books